Traditional and complementary medicine use for knee osteoarthritis - Külekçioğlu, Sevinç (The European Research Journal, 2022)
Objectives: This study aims to determine the traditional and complementary medicine (TCM) use in patients with knee osteoarthritis, by whom these methods are recommended, which methods provide the patients with the best outcome, and to contribute to the awareness of physicians about TCM methods. Methods: One hundred four patients over the age of 40 who were diagnosed with knee osteoarthritis and had complaints for at least 6 months were included in the study. The TCM applications in the previous treatments of the patients, and whether they used additional medications or not, and finally, the TCM method they benefited from the most, and who recommended and applied these methods were questioned and recorded. Results: In our study, we found that the most commonly used treatments were phytotherapy products and supportive drugs, in line with the literature. We did not find the use of hypnosis, hirudotherapy, reflexology, homeopathy, osteopathy, chiropractic, maggot applications, apitherapy, or music therapy methods. TCM methods of patients, we determined that they learned from their families and close circles rather than the doctors they applied to. Conclusions: Patients diagnosed with knee osteoarthritis commonly use TCM methods, phytotherapy being in the first place.